Assembly of the Marburg virus envelope. (20th December 2012) - Mittler, Eva; Kolesnikova, Larissa; Herwig, Astrid; Dolnik, Olga; Becker, Stephan
Summary The key player to assemble the filamentous Marburg virus particles is the matrix protein VP40 which orchestrates recruitment of nucleocapsid complexes and the viral glycoprotein GP to the budding sites at the plasma membrane. Here, VP40 induces the formation of the viral particles, determines their morphology and excludes cellular proteins from the virions. Budding takes place at filopodia in non‐polarized cells and at the basolateral cell pole in polarized epithelial cells. Molecular basis of how VP40 exerts its multifunctional role in these different processes is currently under investigation. Here we summarize recent data on structure–function relationships of VP40 and GP in connection with their function in assembly. Questions concerning the complex particle assembly, budding and release remaining enigmatic are addressed. Cytoplasmic domains of viral surface proteins often serve as a connection to the viral matrix protein or as binding sites for further viral or cellular proteins. A cooperation of MARV GP and VP40 building up the viral envelope can be proposed and is discussed in more detail in this review, as the cytoplasmic domain of GP represents an obvious interaction candidate because of its localization adjacent to the VP40 layer. Interestingly, truncation of the short cytoplasmic domain of GP neither inhibited interaction with VP40 nor incorporation of GP into progeny viral particles. Based on reverse genetics we generated recombinant virions expressing a GP mutant without the cytoplasmic tail. Investigations revealed attenuation in virus growth and an obvious defect in entry. Further investigations showed that the truncation of the cytoplasmic domain of GP impaired the structural integrity of the ectodomain, whichconsequently had impact on entry steps downstream of virus binding. Our data indicated that changes in the cytoplasmic domain are relayed over the lipid membrane to alter the function of the ectodomain.